2019
DOI: 10.1038/s41598-019-46153-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of women with previous caesarean sections: Secondary analysis of World Health Organization Multicountry Survey on Maternal and Newborn Health

Abstract: Secondary analysis of World Health Organization Multicountry Survey on Maternal and Newborn Health (WHOMCS) was undertaken among 173,124 multiparous women to assess the association between previous caesarean sections (CS) and pregnancy outcomes. Maternal outcomes included maternal near miss (MNM), maternal death (MD), severe maternal outcomes (SMO), abnormal placentation, and uterine rupture. Neonatal outcomes were stillbirth, early neonatal death, perinatal death, neonatal near miss (NNM), neonatal intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
(34 reference statements)
5
36
1
Order By: Relevance
“…In contrast to other studies, in which a concern of medically doubtful CSs have been reported among women with higher socio-economic status [9,34,35], we found no association between suboptimal CS indications and ethnicity or education level. In order to avert potentially harmful short-and longterm consequences of unnecessary CSs in low-resource settings [40][41][42], emergency CS indications need to be as accurate as possible and rely on proper proceeding monitoring. A recent systematic review of 37 studies from lowand middle-income countries concludes that low-cost equipment such as Pinard fetoscope, wind-up Doppler, and partograph, preferably combined with clinical information such as meconium stained liquor and fetal scalp stimulation, has the potential to improve outcomes and avoid unnecessary CSs in low-resource settings, hence improving care does not require expensive, high-technology investments [16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies, in which a concern of medically doubtful CSs have been reported among women with higher socio-economic status [9,34,35], we found no association between suboptimal CS indications and ethnicity or education level. In order to avert potentially harmful short-and longterm consequences of unnecessary CSs in low-resource settings [40][41][42], emergency CS indications need to be as accurate as possible and rely on proper proceeding monitoring. A recent systematic review of 37 studies from lowand middle-income countries concludes that low-cost equipment such as Pinard fetoscope, wind-up Doppler, and partograph, preferably combined with clinical information such as meconium stained liquor and fetal scalp stimulation, has the potential to improve outcomes and avoid unnecessary CSs in low-resource settings, hence improving care does not require expensive, high-technology investments [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many obstetricians and women choose a cesarean section as the mode of delivery to avoid these possible complications, even if the long-term neurological outcome of the infants is normal when mothers and fetuses are well selected, and the deliveries are handled with caution [6,7]. This decision might seem controversial, as a cesarean section might cause adverse long-term health problems in the offspring, and the uterus scar created by the cesarean section increases the complication risks for the mother during subsequent pregnancies and deliveries [1,[8][9][10][11][12]. Preceding studies indicate that a history of uterine scarring is associated with maternal hemorrhage, placenta accreta, placenta praevia, uterine rupture, stillbirth, and repeated cesarean section in subsequent pregnancies and deliveries [2,3,13].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Since the measurement of the rates and cases of MNM contributes to the audit of the quality of maternal health care, these results would reflect the interest in the evaluation or development of maternal health surveillance systems worldwide, which corresponds to some articles found on MNM published over the previous years. Other terms reported in more recent studies, such as cesarean section, preeclampsia, severe maternal outcome (smo), termination, case fatality rate, association and potentially life-threatening condition (pltc), as wellas terms that describe countries such as Brazil, Ethiopia, India, and Tanzania reflect that, in recent years, the authors have been conducting studies that measure the cases and rates of MNM according to specific maternal health conditions and their associated factors, [21][22][23][24][25] or studies for the validation of the MNM criteria in these countries. [26][27][28][29] Terms related to severe acute maternal morbidity were not included, since this is a term interchangeable with MNM, and the WHO does not recommend refering to severe, life-threatening obstetric complications.…”
Section: Discussionmentioning
confidence: 99%